"C'mon, Get Happy": The Commodification of Linguistic Stereotypes in a Volkswagen Super Bowl Commercial. (June 2017) - Lopez, Qiuana; Hinrichs, Lars
This article examines a national Volkswagen commercial, broadcast on American television during the 2013 Super Bowl, and the intense public debate that met it. It shows a cheerful European American owner of a 2013 Volkswagen Beetle, who despite being from Minnesota speaks in a Jamaican Creole (JC) accent with features of Rastafarian speech. The focus of analysis is the linguistic performance of the JC as well as the linguistic reception by American and Jamaican audience members. The linguistic analysis reveals that the primary objective in how the character uses forms of JC is not linguistic authenticity, but simply to index Jamaican culture and identity through selective feature use. Our discourse analysis of the ad's reception shows that linguistic ideologies, including ideas about what constitutes linguistic racism, vary widely among American viewers and are generally divided along racial lines. On the other hand, Jamaican viewers were found to have a more homogenous perspective. We conclude that the selection of non-local racialized stereotypes as the target of cross-racial stylization practices complicate, but do not eliminate, modern types of linguistic minstrelsy.